EVALUASI PELAKSANAAN PROBITY AUDIT DALAM RANGKA AKUNTABILITAS PENGELOLAAN DANA SEKTOR PUBLIK - Dharu Wicaksono; Gideon Setyo Budiwitjaksono (Jurnal Proaksi, 2021)
This research is aimed at conducting "Evaluationof The Implementation of Probity Audit in the frameworkof Accountability of Public Sector Fund Management" against Government Agencies that have obligations and tupoksi to conduct probity audits. Methods applied in the discussion apply qualitative methods through the application of inpretive phenomenology. It is used by researchers in order to explore an individual's understanding of his environment and also to understand a person's perspective on a personal experience, especially related to the implementation of probity audits, especially those conducted by the Mojokerto City Inspectorate. The results that can be concludedare about the Probity Audit of procurement of goods and services carried out by the Mojokerto City Inspectorate so far is considered to still require a number of improvements seen from the three stages in the implementation of Probity Audit conducted, namely Planning, Implementation and Utilization of its Report. But the effectiveness of Probity Audit on the procurement of goods and services is considered very effective against public sector fund management accountability in view of the willingness and high awareness from the auditorship of the Mojokerto City Inspectorate and Local Government Organizations (OPD) for the benefits of Goods and Services audit probity activities that have until now been obtained. Keywords: Accountability, Procurement of Goods and Services, Probity Audit